2019
DOI: 10.1093/mnras/stz2513
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the galaxy H i size–mass relation

Abstract: We analytically derive the observed size-mass relation of galaxies' atomic hydrogen (H i), including limits on its scatter, based on simple assumptions about the structure of H i discs. We trial three generic profiles for H i surface density as a function of radius. Firstly, we assert that H i surface densities saturate at a variable threshold, and otherwise fall off exponentially with radius or, secondly, radius squared. Our third model assumes the total gas surface density is exponential, with the H i fracti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 92 publications
7
45
0
Order By: Relevance
“…On the other hand, the optically thin nature of the Hi emission leads to the possibility of probing possible gas inflows via the asymmetry of the line profile (Bournaud et al 2005;Deg et al 2020). The Hi fluxes are found to very closely follow scaling relations such as the star formation rate (SFR) surface density Σ SFR and the combined surface density of molecular (H 2 ) and Hi gas, Σ HI +H 2 (Schmidt 1959;Kennicutt 1998), Hi mass versus stellar mass (Huang et al 2012;Maddox et al 2015;Romeo 2020), Hi mass versus Hi size (Wang et al 2016;Stevens et al 2019), and the Hi-to-H 2 ratio as a function of stellar or gas surface density (Leroy et al 2008). These relations enable us to reveal important information even when we are unable to perform spatially resolved Hi observations (Giovanelli & Haynes 2015).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, the optically thin nature of the Hi emission leads to the possibility of probing possible gas inflows via the asymmetry of the line profile (Bournaud et al 2005;Deg et al 2020). The Hi fluxes are found to very closely follow scaling relations such as the star formation rate (SFR) surface density Σ SFR and the combined surface density of molecular (H 2 ) and Hi gas, Σ HI +H 2 (Schmidt 1959;Kennicutt 1998), Hi mass versus stellar mass (Huang et al 2012;Maddox et al 2015;Romeo 2020), Hi mass versus Hi size (Wang et al 2016;Stevens et al 2019), and the Hi-to-H 2 ratio as a function of stellar or gas surface density (Leroy et al 2008). These relations enable us to reveal important information even when we are unable to perform spatially resolved Hi observations (Giovanelli & Haynes 2015).…”
Section: Introductionmentioning
confidence: 78%
“…We can roughly estimate the dynamical mass based on the Hi FWHM, and Hi radius (R Hi ) by M Hi dyn = (FWHM/2/ sin θ) 2 R Hi /G, where θ is the Hi inclination angle and R Hi is the Hi radius. Since for galaxies the Hi size is tightly correlated with the Hi mass (Wang et al 2016;Stevens et al 2019), the R Hi can be estimated from M Hi using the relation derived by Wang et al (2016). For the Hi mass range of 9.5 < log(M Hi /M ) < 10, the Hi radius is in the range of 16.5 to 30 kpc (see Eq.…”
Section: Dynamical Massesmentioning
confidence: 99%
“…We can compare these radii to the observed H size-mass relation, R 1 = M HI /12.88 where R 1 in pc is the radius at which the surface density drops to 1 M pc −2 , and M HI is in solar masses (Stevens et al 2019b). This gives, for log M HI = [8, 9, 10, 11], 8, 8.8, 28, 88] kpc.…”
Section: Comparison Of Modelsmentioning
confidence: 99%
“…b See also Stevens et al (2019b) for an extensive discussion on the origin of the small observed scatter of the HI mass versus HI size relation.…”
Section: Definitions Based On Colour and Structural Propertiesmentioning
confidence: 99%